Needlestick Injury Factor Data Analysis: Basis for Developing Policies and Training Programs among Healthcare Workers in Bo Government Hospital - Exton Mohamed Zoker; Osman Thullah; Samuel Karim (FOUNDAE (Foundation of Advanced Education), 2023)
This study aims to assess the prevalence and contributing factors of needlestick and sharps injuries (NSIs) among healthcare workers (HCWs) at Bo Government Hospital, Southeast Sierra Leone. The primary objective is to identify key risk factors and evaluate the effectiveness of current safety protocols in reducing NSI incidents in the main operating theater and theater complex. A descriptive cross-sectional study was conducted involving 60 randomly selected HCWs, including doctors, nurses, and support staff. Data were collected through structured interviews using a questionnaire that addressed demographics, knowledge of blood-borne diseases, adherence to standard precautions, and experience with NSIs. The data were analyzed using descriptive statistics to identify trends and associations between NSI occurrences and various occupational factors. The study revealed that 60% of the respondents had experienced NSIs, with a significant proportion attributing incidents to factors such as inadequate training, improper use of protective equipment, and high workload. Despite awareness of reporting mechanisms, only 40% of those affected reported their injuries to the appropriate authorities. The findings highlight the need for enhanced training programs, improved safety protocols, and more robust reporting systems to mitigate the risk of NSIs and ensure the safety of HCWs. This study underscores the urgent need for targeted interventions to reduce NSIs, thereby protecting HCWs from potential exposure to blood-borne pathogens and improving overall patient care quality in the hospital.